Subjective formula in Holy Quran Morphological study - ناظم حميد جنان; عبد المهديّ حسين (Al-Adab Journal, 2018)
The research topic is summarized in to two subjects : the first revocation of the possibility and multiples in finding out the vocalization content of holy Quran, for holy Quran is one book conveys by one God and descended one angel to the heart of one prophet and its pronunciations are one and integrated for each one meaning illustrating not suspicious multiples from where the possible and licit instruction? And the matter of revocation set out from three morphological phenomena( morphological transformation, arbitrated direction and the linguistic Ejaz-ul-Quran) , revocation of the morphological transformation of all its types and examples in holy Quran and Arabic in general in the state revocation of morphological possibility structure roof, because the interpretational aspects are not multiples for the single interpreter unless depending on the transformational phenomenon in the morphological formulas which the researcher opines that they are type of deviation of the saying from its content , then revocation of the arbitrated direction represented by presumption of omissions in Quran vocabulary structure and its general context in the place of revocation of possible interpretation walls, because saying with omission, mentioning, estimation, dissimilation, increase , decrease and putting first and at last all represented approvals of the arbitrated interpretation which observe the integrity of Ejaz-ul-Quran text related with its pronunciation preserved in its content as it is without presumption - during its interpretation- without decrease or increase of it. As for the another matter in which the research deals with construction to replace the decisive morphology by morphological possibility and the licit direction( the intentional direction) depending on the linguistic Ejaz-ul-Quran represented by maintain the vocalization structure as in the holy Quran without saying it is transformed from one syntax including pronunciation without saying: it is structure from which one pronunciation or more. And for the multiples of holy Quran pronunciations which are possibly morphological interpreted , the research elected ten of them for the morphological analysis come in the objective form of where he opines that they are sufficient for the clarity of the main thought which is revocation of possible interpretation of holy Quran interpretation according to content of holy Quran in illustrated Ejaz-ul-Quran which is not realized in the interpretation aspects as whole but in one of them and these pronunciations are( Baqiya, Al-Haqaa,Kheina, Khataia,Khalisaa, Shakilaa,Aqibaa ,Kashifaa, Kafaa, Nadhiraa).